Linking information and consultation procedures at local and European level - Dorssemont, Filip; Kerckhofs, Peter (Luxembourg, 2015)
"This report examines the differences in alignment, timing and content of workplace information and consultation processes at national and European level. It compares the legal situation at national and European level in six EU Member States: Belgium, France, Germany, Italy, the Netherlands and the UK. It finds that the provisions of the EU directive governing the operation of European Works Councils are ambiguous about the order in which information and consultation processes should happen at each level. It also highlights the fact that EU Member States have interpreted the directive in different ways when transposing it into national law. The report concludes with a number of pragmatic guidelines as to how this issue might be resolved."